Delineation of high nature value areas in Hungary - Barnáné Belényesi, Márta; Podmaniczky, László (JOURNAL OF LANDSCAPE ECOLOGY, 2007)
In the European Union the concept of High Nature Value (HNV) farmlands and farming methods has developed for the past 15 years and it is in tight connection with the goal of integrating environmental interests into EU policies. Idea of HNV farming links together protection of biodiversity, conservation of rural and natural values by keeping agricultural areas under long-term cultivation and supporting special farming systems. These areas are currently under delineation in the member states of the European Union. We completed the designation of Hungarian HNV areas by considering, and to a certain degree modifying, the European Union’s methodological recommendation, based on national data bases. Results had been contrasted with spatial location of areas protected, or currently supported by certain agri-environmental payments, because these systems are assigned as conservation tools of HNV areas. Results are reassuring, showing that new nature conservation and agricultural policy of the EU were taken into consideretion by hungarian experts during agri-environmental payment system formulation.
Keywords: high nature value areas; environmentally sestive areas; GIS